Gravity, distance, and traffic flows in Mexico - Duran-Fernandez, R; Santos, G (Elsevier, 2014)
This paper presents an econometric analysis that compares the performance of different measures of distance in a gravity model using state data for Mexico. The estimation shows that at this geographic scale, the definition of distance does not affect the explanatory power of the model significantly. However, time-based definitions of distance have a marginal improvement on the model fit in comparison to length-based measures. When geographic specific fixed effects are unknown, the model shows that distance measured as road network distance is a better predictor. The paper concludes that time-based definitions of distance present several advantages in comparison to traditional length-based definitions. However, at large geographic scales, where relative distances between every geographic unit are long, the use of length-based distance instead of time-based distance to approximate travel costs generates similar results.